2020
DOI: 10.1021/acs.energyfuels.0c02086
|View full text |Cite
|
Sign up to set email alerts
|

Flue Gas Recirculation during Biomass Combustion: Implications on PM Release

Abstract: The need for low-emission technologies in biomass domestic heating systems has encouraged the development of primary methods to improve the combustion process. Air-injection strategies are known to yield successful results regarding gaseous emissions; however, their implication on PM release still has some unknowns. This research analyzes how the concentration, types, and morphology of released particles can be affected by the air staging distribution and flue gas recirculation. This study was carried out in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…While the use of natural gas, hydrogen, and light oil in FIR burners has been extensively studied and reported, alternative fuel sources, including liquefied petroleum gas, synthetic gas, heavy oil, and biomass fuel, have received relatively less attention in the literature. The report includes natural gas burners, light oil burners, dual fuel burners for natural gas and hydrogen, and dual fuel burners for natural gas and light oil. , The integrations of FGR technology in biomass fuel and waste (municipal solid waste and industrial waste) combustion systems have emerged as a crucial factor in reducing fuel-NOx emissions. A novel approach that has shown promising results involves the synergistic combination of high-oxygen waste fuels and FGR .…”
Section: Challenges Research Gaps and Perspectivesmentioning
confidence: 99%
“…While the use of natural gas, hydrogen, and light oil in FIR burners has been extensively studied and reported, alternative fuel sources, including liquefied petroleum gas, synthetic gas, heavy oil, and biomass fuel, have received relatively less attention in the literature. The report includes natural gas burners, light oil burners, dual fuel burners for natural gas and hydrogen, and dual fuel burners for natural gas and light oil. , The integrations of FGR technology in biomass fuel and waste (municipal solid waste and industrial waste) combustion systems have emerged as a crucial factor in reducing fuel-NOx emissions. A novel approach that has shown promising results involves the synergistic combination of high-oxygen waste fuels and FGR .…”
Section: Challenges Research Gaps and Perspectivesmentioning
confidence: 99%
“…Both biomass and its pyrolysis-derived char are excellent feedstock for renewable electricity generation via direct combustion and/or co-combustion in existing coal-fired power stations. Under such applications, the removal of alkali and alkaline-earth metallic (AAEM) species inherently presented in these solid biofuels is often required to mitigate ash-related operational problems such as corrosion, ash deposition, and fine particulate matter emission. Removal of AAEM species in biomass has been achieved via leaching with water, mineral acids, and organic acids . Taking rice straw as an example, 80.4%–88.8% of Na, 82.3%–99.8% of K, 33.5%–99.2% of Mg, and 17.1%–97.9% of Ca are leached out with various types of leaching agents (water, acetic acid, and mineral acids) .…”
Section: Introductionmentioning
confidence: 99%
“…Flue gas recirculation (FGR) consists of replacing a portion of the primary air with flue gas that has previously been cooled, to reduce the oxygen concentration and, thus, reducing the temperature of the fuel bed and slowing its thermal conversion process. Studies have shown how FGR helps to reduce the unburnt species, PM and NOx emissions, and the slagging in the bed [12][13][14][15]. Bed cooling solutions consist of the refrigeration of the solid fuel bed.…”
Section: Introductionmentioning
confidence: 99%
“…To allow the characterization of the temperature distribution inside the combustion system and the pollutant emissions, the plant is equipped with thermocouples located in different zones, as well as a gas analyzer and a low-pressure impactor connected to the exhaust. Several experimental studies have already been carried out, testing the stability and repeatability of the facility, and analyzing the effectiveness of using different air ratios, FGR and bed cooling for reducing pollutant emissions [13,14,18,19].…”
Section: Introductionmentioning
confidence: 99%